Predicting personality : using AI to understand people and win more business - D'Agostino, Andrew; Skloot, Greg (John Wiley & Sons, Inc., 2020)
"As the world has become hyper-connected, people have become hyper-skeptical, and communication has actually gotten much harder. As connected as we are, attention spans are shrinking, trust is dwindling, and growth is less guaranteed. An exciting new branch of artificial intelligence--Personality AI--is setting out to change that: marrying traditional machine learning, data analytics, and behavioral psychology, Personality AI helps professional communicators break through the noise with empathy and build trust with their audience, leveraging data to accelerate trust, build relationships, and win more customers. The proposed title is the playbook for anyone whose livelihood or business is built on their ability to communicate effectively and build teams. Exploring the next generation of human communication, Crystal co-founder and CEO Drew D'Agostino exposes how businesses can reap the benefits of AI and machine learning today, not tomorrow. Readers will not only learn what Personality AI is and how it works, but direct applications in business, life, and how to understand personality types in context--sales, recruiting, coaching, and more. D'Agostino also presents important considerations that using Personality AI brings up in ethics and compliance conversations, plus guidelines for any company that wants to use their people data to learn and execute . This book provides practical guidelines for using this technology to accelerate growth, strengthen relationships, communicate more effectively, and win more business"--